Social Participation and Spatial Flexibility in the Mappetuada Tradition of Wotu, East Luwu Regency - Ermywati HR; Wildha Mardhatillah; Endah Ciptaning Puspitasari (The Future of Education Journal, 2026)
Wotu Subdistrict is one of the subdistricts in East Luwu Regency that still maintains communal space in everyday life, so that changes in public-private zoning take place flexibly, particularly during certain communal events. The mappetuada tradition is one of the customs in Wotu Subdistrict that generally shows a fairly high degree of spatial flexibility, with zoning changes occurring on a daily basis as the event approaches. This study therefore aims to identify the spatial flexibility that occurs during the mappetuada tradition and to analyze the factors that influence this highly flexible spatial change. An evaluative descriptive method was used. Interview data show that spatial flexibility during the mappetuada tradition produces changes in public-private zoning. This spatial flexibility occurs because of the need for additional space and the value placed on trust and communal togetherness